The HLA Class II Associations with Rheumatic Heart Disease in South Indian Patients: A Preliminary Study - Bajoria, Divya (JCDR Research and Publications (P) Limited, 2013)
Introduction: Rheumatic heart disease (RHD) occurs in 30-45% of the patients with rheumatic fever (RF) and it leads to chronic valvular lesions. The human leukocyte antigen (HLA) might confer a susceptibility to RHD. The aim of the present study was to determine the prevalent HLA class II DR/DQ allelic types which were associated with rheumatic heart disease (RHD) in a small group of south Indian patients and to compare them with those in the control subjects. Methods: A total of 23 patients who were diagnosed with RHD and 6 control samples were included in this study. A low resolution HLA Class II DR/DQ typing was performed on the blood samples by the PCR-SSP method. Results and Conclusion: The DRB3*01:01:02:01 allele showed a positive association with RHD, whereas the DQB1 loci alleles did not show any significant association.